Impact of Social Interaction and FOMO on Adolescent Mental Health in the Digital Age - Diwyami, Ni Putu; Widyandari, Ni Made Ayu Sukma; Narlianti, Ni Putu Veny (Babali Nursing Research, 2025)
Background: Social interaction in the digital era shapes adolescents' mental well-being. While online platforms promote social connection, they also increase exposure to cyberbullying, social pressure, and Fear of Missing Out (FOMO), which may lead to psychological distress. This study investigated how social interaction and FOMO simultaneously affect adolescents' mental health in Bali. Methods: This cross-sectional study examined the relationship between social interaction, FOMO, and adolescent mental health among 345 adolescents aged 10–18 in Bali Province. Participants were active social media users recruited through consecutive sampling. Data were collected using a validated 106-item Likert-scale questionnaire (Cronbach's α = 0.968) and analyzed using logistic regression with a significance level of p < 0.05. Results: Multivariate analysis showed that poor face-to-face interaction (AOR = 9.75; 95% CI: 4.99–19.03; p = 0.036), high online interaction (AOR = 17.10; 95% CI: 8.51–33.99; p = 0.001), and identified FOMO status (AOR = 6.13; 95% CI: 3.36–11.16; p = 0.018) were significantly associated with higher psychological distress among adolescents. Conclusion: A combination of reduced in-person social interaction, excessive online engagement, and FOMO substantially increases the risk of mental health problems in adolescents. Limited offline interaction restricts emotional support and social validation, while high online activity and FOMO contribute to anxiety, social comparison, and feelings of exclusion. These findings highlight the importance of promoting balanced social interaction and digital literacy in the digital age to support adolescent mental health.